A Sieve‐Functional and Uniform‐Porous Kaolin Layer toward Stable Zinc Metal Anode. (16th March 2020) - Deng, Canbin; Xie, Xuesong; Han, Junwei; Tang, Yan; Gao, Jiawei; Liu, Cunxin; Shi, Xiaodong; Zhou, Jiang; Liang, Shuquan
Abstract: Zinc metal is considered as one of the best anode choices for rechargeable aqueous Zn‐based batteries due to its high specific capacity, abundance, and safety. However, dendrite and corrosion issues remain a challenge for this system. Herein, sieve‐element function (selective channel of Zn 2+ ) and uniform‐pore distribution (≈3.0 nm) of a kaolin‐coated Zn anode (KL‐Zn) is proposed to alleviate these problems. Based on the artificial Zn metal/electrolyte interface, the KL‐Zn anode not only ensures dendrite‐free deposition and long‐time stability (800 h at 1.1 mA h cm −2 ), but also retards side reactions. As a consequence, KL‐Zn/MnO2 batteries can deliver high specific capacity and good capacity retention as well as a reasonably well‐preserved morphology (KL‐Zn) after 600 cycles at 0.5 A g −1 . This work provides a deep step toward high‐performance rechargeable Zn‐based battery system. Abstract : The self/electrochemical corrosion and the formation of dendrites can be effectively suppressed via a sieve‐functional and uniform‐porous kaolin coating on the surface of bare Zn, which can modulate the Zn 2+ plating/stripping process and isolate the bulk electrolyte from the bare Zn. Uniform deposition of zinc ions and good cycling performance of the cells with kaolin‐coated Zn anode (KL‐Zn) is achieved.